Strategi Penanaman Nilai-Nilai Persatuan dan Kesatuan Pada Siswa - Yurisdika, Aulia Dyah (Sekolah Tingi Keguruan dan Ilmu Pendidikan (STKIP) PGRI Tulungagung, 2019)
The purpose of this research is to describe the strategy of PPKn teachers in instilling unity and unitary values to students, describing how the teacher of PPKn in implementation strategies in instilling unity and unitary values to students, and described the outcome of implementing strategy conducted by PPKn teachers in instilling unity and unitary values to students. The method used in this research is a qualitative method of description. Data collection is done by interview, observation, and documentation research. The interview was conducted to PPKn teachers and students of grade VIII-1 SMP Negeri 63 Jakarta. As well as with two key informant that is curriculum and the principal of SMP Negeri 63 Jakarta. The results of the research showed the strategy of PPKn teachers in instilling unity and unitary, is the strategy used by PPKn teachers in instilling the values of unity and unitary in students is expository strategy and Discovery inquiry. The PPKn teacher's strategy has been well implemented and there are changes student behaviour in class VIII. Keywords: strategy, Instilling, Unity and Unitary Values